2017
DOI: 10.19082/5244
|View full text |Cite
|
Sign up to set email alerts
|

Salivary flow rate and xerostomia in patients with type I and II diabetes mellitus

Abstract: BackgroundDiabetes mellitus is one of the most prevalent metabolic diseases, with complications such as decreased salivary flow rate and xerostomia.ObjectiveThis study aimed to determine the salivary flow rate and xerostomia in type I and II diabetic patients in comparison with healthy controls.MethodsThis case-control study was performed on diabetic patients of a private office in Babol, Iran, between May 2015 and October 2016. This study involved two study groups (type I and II diabetes, with 40 in each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 20 publications
4
34
1
2
Order By: Relevance
“…Diabetes is one of the most prevalent metabolic diseases affecting millions of people (Cho et al , 2018). Dry mouth is a common complication of diabetes (Hoseini et al , 2017; Carramolino‐Cuellar et al , 2018; Pedersen et al , 2018). Studies show that the prevalence rate of dry mouth is up to 30%–80% in diabetes patients and only 10%–30% in healthy subjects (Carda et al , 2006; Ivanovski et al , 2012; Malicka et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is one of the most prevalent metabolic diseases affecting millions of people (Cho et al , 2018). Dry mouth is a common complication of diabetes (Hoseini et al , 2017; Carramolino‐Cuellar et al , 2018; Pedersen et al , 2018). Studies show that the prevalence rate of dry mouth is up to 30%–80% in diabetes patients and only 10%–30% in healthy subjects (Carda et al , 2006; Ivanovski et al , 2012; Malicka et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not report significant complaints of xerostomia (Chávez et al, 2001). Hoseini et al (2017) also reported lower salivary flow rate and higher xerostomia in DM patients compared to healthy controls. The underlying aetiology of xerostomia may be due to systemic diseases such as endocrine, autoimmune, infectious, and granulomatous diseases (Millsop et al, 2017).…”
Section: Introductionmentioning
confidence: 83%
“…The majority of subjects who experienced coated tongue were poor glycemic control level group (Table 2). Glycemic control plays a key role in the initiation and development of many signs and symptoms [14]. Previous studies have shown a decrease in salivary secretion in diabetes mellitus patients with poor glycemic control levels compared with the good and moderate glycemic control levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among the several reasons which contribute to the decreased salivary flow rate in diabetes mellitus patients are pathologic changes in the structure of salivary glands neuropathy of the sympathetic and parasympathetic system, and microvascular disorders that disrupt saliva production. Additionally, following the hyperglycemia and glucosuria, body fluids are more excreted, and subsequently, secretion of saliva is reduced [14].…”
Section: Discussionmentioning
confidence: 99%